2018
DOI: 10.3390/ma11061043
|View full text |Cite
|
Sign up to set email alerts
|

Wear Resistance of 3D Printing Resin Material Opposing Zirconia and Metal Antagonists

Abstract: 3D printing offers many advantages in dental prosthesis manufacturing. This study evaluated the wear resistance of 3D printing resin material compared with milling and conventional resin materials. Sixty substrate specimens were prepared with three types of resin materials: 3D printed resin, milled resin, and self-cured resin. The 3D printed specimens were printed at a build angle of 0° and 100 μm layer thickness by digital light processing 3D printing. Two kinds of abraders were made of zirconia and CoCr allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 28 publications
3
55
0
1
Order By: Relevance
“…Moreover, in vitro studies have demonstrated that CoCr materials fabricated by SLM still had clinically acceptable marginal gap between ceramic and metal frameworks and metal-ceramic bond strength even after ceramic firing. This further highlights CoCr alloy as a promising material for 3D printed dental prostheses using 3D printing techniques, such as SLM [ 26 , 47 , 49 , 51 , 52 ].…”
Section: Biomaterials Used In Dental 3d Printingmentioning
confidence: 99%
“…Moreover, in vitro studies have demonstrated that CoCr materials fabricated by SLM still had clinically acceptable marginal gap between ceramic and metal frameworks and metal-ceramic bond strength even after ceramic firing. This further highlights CoCr alloy as a promising material for 3D printed dental prostheses using 3D printing techniques, such as SLM [ 26 , 47 , 49 , 51 , 52 ].…”
Section: Biomaterials Used In Dental 3d Printingmentioning
confidence: 99%
“…The 3D-printing technology used in dentistry is classified into four main categories: extrusion printing, inkjet printing, laser melting/sintering, and stereolithography printing [ 3 ]. Those printing methods are based on the principle of layered manufacturing, which is more suitable than conventional casting and milling methods for producing individualized complex structures [ 6 ]. Moreover, using a machining process with computer-aided design/computer-aided manufacturing (CAD/CAM) reduces manual labor and material waste [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, using a machining process with computer-aided design/computer-aided manufacturing (CAD/CAM) reduces manual labor and material waste [ 1 ]. Recent studies have shown that 3D-printed dental prostheses had a clinically acceptable degree of precision [ 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCL and PLA are biodegradable synthetic materials for FDM that have superior mechanical strengths, and comparable biocompatibilities (19,20). PMMA-resin is a photo-curable, 3D-printable resin for DLP, which offers many advantages in dental prosthesis manufacturing, such as 3D-printed artificial teeth, denture bases, provisional crowns, and dental bridge material (13,14,(21)(22)(23)(24). As TT is an indwelling catheter placed in the tracheal lumen, chemical and mechanical changes of the tube as well as biofilm formation are important factors for determining safety for clinical application.…”
mentioning
confidence: 99%